A New T. gondii Mouse Model of Gene-Environment Interaction Relevant to Psychiatric Disease. (2nd December 2018) - Kannan, Geetha; Prandovszky, Emese; Severance, Emily; Yolken, Robert H.; Pletnikov, Mikhail V.
Abstract : Infection with the protozoan parasite, Toxoplasma gondii ( T. gondii ), was linked to several psychiatric disorders. The exact mechanisms of a hypothesized contribution of T. gondii infection are poorly understood, and it appears that only a subset of seropositive individuals go on to develop a mental illness, suggesting genetic vulnerability. In order to stimulate mechanistic studies of how exposure to T. gondii could interact with genetic predisposition to psychiatric disorders, we have generated and characterized a mouse model of chronic T. gondii infection in BALB/c mice with inducible forebrain neuronal expression of a C-terminus truncated dominant-negative form of disrupted-in-schizophrenia 1 (DN-DISC1). In this gene-environment interaction (GxE) model, exposing control and DN-DISC1 male and female mice to T. gondii produced sex-dependent abnormalities in locomotor activity and prepulse inhibition of the acoustic startle. No genotype- or sex-dependent effects were found on levels of anti-Toxoplasma IgG antibodies or anti-NMDAR or C1q antibodies. Our work demonstrates that a psychiatric genetic risk factor, DN-DISC1, modulates the neurobehavioral effects of chronic T. gondii infection in a sex-dependent manner. The present T. gondii model of GxE provides a valuable experimental system for future mechanistic studies and evaluation of new treatments.